Social Interactivity in Live Video Experiences Reduces Loneliness - Kaveladze, Benjamin T.; Morris, Robert R.; Dimitrova-Gammeltoft, Rosa Victoria; Goldenberg, Amit; Gross, James J.; Antin, Judd; Sandgren, Melissa; Thomas-Hunt, Melissa C. (Frontiers in Digital Health, 2022)
Background: Loneliness, especially when chronic, can substantially reduce one’s quality of life. However, positive social experiences might help to break cycles of loneliness by promoting more prosocial cognitions and behaviors. Internet-mediated live video communication platforms (eg Zoom and Twitch) may offer an engaging and accessible medium to deliver such social experiences to people at scale. Despite these platforms’ widespread use, there is a lack of research into how their socially interactive elements affect users’ feelings of loneliness and connection. Objective: We aimed to experimentally evaluate whether socially interactivity in live video experience improves loneliness-related outcomes. Materials and Methods: We recruited participants from an online survey recruitment platform and assigned half to participate in a socially interactive live video experience with 6-12 strangers and the other half to a non-interactive control experience that was designed to be identical in every way but not socially interactive. Participants completed several baseline self-report measures of psychosocial well-being, participated in the hour-long video experience (an entertaining astronomy lesson), and then completed some baseline measures again. Four weeks later, we followed up with participants to evaluate their change in trait loneliness since baseline. We pre-registered our hypotheses and analysis plan and provide our data, analysis code, and study materials online. Results: 249 participants completed the initial study and met inclusion criteria, 199 of whom also completed the 4-week follow-up. Consistent with our predictions, we found that directly after the more socially interactive experience, participants’ feelings of connectedness increased more (p<.001), positive affect increased more (p=.002), feelings of loneliness decreased more (p<.001), social threat decreased more (p=.006), and negative affect decreased more (p=.003) than they did after the less interactive experience. However, change in trait loneliness between baseline and 4 weeks later did not differ between conditions (p=.953). Conclusions: Including socially interactive components in live video experiences can improve loneliness-related psychosocial outcomes for a short time. Future work should explore leveraging these benefits towards longer-term prosociality. Future work can also identify if the effects we observed generalize across different populations and kinds of online experiences.